Describing and characterizing the WAK/WAKL gene family across plant species: a systematic review - Harvey, Aaron; van den Berg, Noëlani; Swart, Velushka (Frontiers in Plant Science, 2024)
Wall-associated kinases (WAKs) and WAK-likes (WAKLs) are transmembrane pectin receptors which have seen rising interest in recent years due to their roles in stress responses and developmental pathways. Consequently, the genes encoding these proteins are continuously identified, described and characterised across a wide variety of plant species. The primary goal of characterizing these genes is to classify, describe and infer cellular function, mostly through in silico methods. However, inconsistencies across characterizations have led to discrepancies in WAK/WAKL definitions resulting in sequences being classified as a WAK in one study but as a WAKL or not identified in another. The methods of characterization range widely with different combinations of analyses being conducted, to similar analyses but with varying inputs and parameters which are impacting the outputs. This review collates current knowledge about WAK/WAKL genes and the recent characterizations of this family and suggests a more robust strategy for increased consistency among the different gene members, as well as the characterizations thereof.